L'interprétation arbitrale du contrat de commerce international - Arfaoui, Besma (Université de Limoges, 2008)
En interprétant le contrat, l'arbitre du commerce international a forgé un certain nombre de principes généraux qui consolident l'édification d'un corps de normes spécifiques au besoin de la communauté internationale des commerçants. Les principes généraux de la lex mercatoria font de l'arbitre une source de droit objectif. A ce premier volet sur lequel débouche l'approche interprétative de l'arbitre s'ajoute le second aspect de l'apport de l'interprétation du contrat. Ce second aspect met en exergue le rôle de l'arbitre en tant que source de droits subjectifs attachée à la détermination des prérogatives et des obligations respectives des parties. A travers cette détermination s'ouvre le débat relatif à l'étendue du pouvoir de l'arbitre à l'égard du contrat. La dimension créative de l'arbitre s'accentue à travers un contrôle restreint des juridictions étatiques. Ce contrôle fait de la sanction de la dénaturation commise par l'arbitre et de la révision au fond de la sentence des interdits à ne pas franchir. Interpreting the contract, the arbitrator of international commerce built up a number of general principles that consolidate the building of standards specific to the needs of the traders' international community. The general principles of Lex Mercatorea make of the arbitrator an objective law source. In addition to this constituent resulted by the interpretative approach of the arbitrator, there is the second aspect which the arbitration interpretation of the international commerce contract comes out with. This aspect highlights the role of arbitrator as a source of subjective laws, a role related to the determination of prerogatives and obligations respective to the parties. This determination leads to a debate relative to the range of powers of the arbitrator with regard to the contract. The creative dimension related to the interpretative approach of the arbitrator becomes more pronounced with the restricted control of state jurisdictions. This control controls the distortion committed by the arbitrator and the revision in the sentence of the proscription not to get over.
Keywords: Arbitrage; Arbitrage (droit international privé); Arbitragem; Arbitration; Commerce international; Commercial Law; Droit commercial; Droit international; International Trade; International law; Lex mercatoria

La clause de médiation - Huchet, Guillaume (Université Jean Moulin Lyon 3, 2007)
La clause de médiation est une stipulation qui a pour objet le règlement amiable des conflits apparaissant au cours de la vie d'un contrat. En ce sens, les parties contractantes s'obligent lors de la survenance d'un différend à mettre en oeuvre préalablement à toute action en justice, un processus de médiation, afin de trouver sous l'égide d'un médiateur une solution amiable. La clause de médiation est une stipulation originale, car elle a un objet duel à la fois contractuel et processuel. Elle comporte en effet un engagement de ne pas agir en justice et une obligation de négocier. Pour permettre une négociation utile, la clause de médiation suspend le droit d'action de chacune des parties. Toute action en justice exercée au mépris de cet engagement entraîne le prononcé d'une fin de non-recevoir ; l'action est dite prématurée. L'obligation de négocier peut se définir comme l'obligation par laquelle les parties s'engagent dans un premier temps à mettre en place le processus de médiation par la désignation d'un médiateur puis à conclure un protocole de mission. Elles devront ensuite s'efforcer de négocier, dans un esprit de bonne foi et de loyauté, une éventuelle solution amiable. Le processus de médiation prendra alors fin soit par la conclusion d'un accord de conciliation, généralement une transaction, soit par le constat d'un échec permettant alors aux parties de retrouver leur liberté d'agir en justice.
Keywords: Contrats; MARD; Mediación; Mediation; Mediação; Médiateur; Médiation; Procédure (droit); Règlement de conflits

La responsabilité de l'arbitre - Sorrente, Jean-Yves (Université Jean Moulin Lyon 3, 2007)
L'arbitrage est une institution de nature contractuelle. II est donc de coutume d'aborder les questions de responsabilité liées à cette activité sous l'angle exclusivement contractuel. Néanmoins, l'arbitre remplit une fonction juridictionnelle qui doit être préservée de toute interférence extérieure. De fait, la responsabilité de l'arbitre relève aussi bien du domaine disciplinaire, pénale, contractuel que délictuel. Aussi, l'étude de sa responsabilité doit-elle aborder ces différents aspects, tout en tenant compte de la nécessaire immunité dont doit bénéficier l'arbitre pour accomplir sa mission, sans pour autant jouir d'une totale impunité. Arbitration is a contractual institution. It is usual to approach questions of the arbitrator's responsibility only under the contractual aspect. Nevertheless, the arbitrator fills a jurisdictional function that must be preserved of exterior interference. The responsibility of the arbitrator concern just as well many domains: disciplinary aspect, criminal and civil liability. Also, the study of his responsibility must she approach these different aspects, all while taking account of the necessary immunity of which must profit the arbitrator to accomplish his mission, without for as much to enjoy a total impunity.
Keywords: Arbitrage; Arbitrage (droit); Arbitragem; Arbitration; Arbitres; Arbitres (droit); Immunité pénale; Responsabilité contractuelle; Responsabilité délictuelle

L'intervention du juge canadien avant et durant un arbitrage commercial international - Bachand, Frédéric (Université de Montréal ; Université Paris 2, 2004)
Cette thèse précise les conditions dans lesquelles les tribunaux judiciaires canadiens peuvent intervenir avant ou durant un arbitrage commercial international, soit afin d'y prêter assistance, soit afin d'en contrôler la légalité. Elle soumet également ces conditions à l'analyse critique, dans le but d'esquisser une théorie générale de l'intervention avant et durant un arbitrage commercial international des juges oeuvrant dans les États qui ont choisi d'accorder leur concours à la justice arbitrale internationale. Principalement, cette théorie repose sur l'idée selon laquelle l'intervention judiciaire survenant avant le prononcé de la sentence ne doit - à quelques exceptions près - servir que les intérêts des opérateurs du commerce international, les intérêts publics prépondérants ne devant être pris en compte que dans l'élaboration des conditions de l'intervention judiciaire survenant après le prononcé de la sentence. De cette idée directrice découlent deux conséquences majeures. D'abord, les ordres juridiques des États qui accordent leur concours à la justice arbitrale internationale doivent être perméables à des faits normatifs transnationaux qui s'intéressent à l'intervention judiciaire avant et durant un arbitrage commercial international, car l'adoption d'une loi ayant vocation à régir spécialement l'arbitrage commercial international ne peut jamais - à elle seule - assurer que les tribunaux judiciaires agiront de manière pleinement satisfaisante. Ensuite, les conditions de cette intervention doivent surtout avoir pour objectif d'accroître l'efficacité - envisagée du point de vue des opérateurs du commerce international - de ce système de justice internationale. This thesis sets out the conditions under which Canadian courts can intervene prior to and during an international commercial arbitration, either to assist the arbitral process or to control its legality. These conditions are also analyzed in a critical manner, with a view to elaborating a general theory of judicial intervention prior to and during an international commercial arbitration in States that have chosen to support international arbitral justice. This theory essentially rests on the idea that judicial intervention occurring before the rendering of the award must almost entirely be geared towards satisfying the interests of international business operators, as superior public interests need only be reflected in the conditions under which courts may intervene after an award has been rendered. Two major consequences flow from this idea. Firstly, the legal orders of States that have chosen to support international arbitral justice must be permeable to transnational normative facts which relate to judicial intervention prior to and during an international commercial arbitration, as the adoption of legislation dealing specifically with international commercial arbitration can never - in itself - ensure that courts will act in a fully satisfactory manner. Secondly, the conditions of such intervention must essentially be aimed at increasing the efficiency - assessed from the point of view of international business operators - of this system of international justice.
Keywords: Arbitrage commercial international; Arbitration; Canadian law; Civil procedure; Comparative law; Droit canadien; Droit comparé; Droit international privé; Droit judiciaire privé; International commercial arbitration; Intervention judiciaire; Judicial intervention; Loi type de la CNUDCI; Private international law; UNCITRAL Model Law

Essays on Bargaining with Outside Options - Adamuz Peña, Mercedes (Universitat Autònoma de Barcelona, 2002)
Los modelos de negociación con opciones exteriores normalmente suponen que los pagos de estas opciones son independientes de las acciones que los negociadores toman durante el proceso negociador. Sin embargo, en muchos contextos, la opción exterior depende de lo que las partes hagan durante la fase negociadora. Uno de estos contextos es el de aquellas negociaciones que se llevan a cabo en presencia de un árbitro. Esta tesis realiza algunas contribuciones a la teoría de la negociación con opciones exteriores, enfatizando aquellas situaciones donde las opciones exteriores aparecen por la intervención de árbitros. En el capítulo 2 analizo los efectos del arbitraje en las negociaciones cuando su uso es voluntario. Considero un modelo de negociación por concesiones donde las partes tienen la posibilidad de llamar a un árbitro con el consentimiento del oponente. Demuestro que la introducción del arbitraje distorsiona el resultado de la negociación. Esta distorsión depende de los costes relativos de implementar una partición mediante un proceso negociador versus un proceso arbitral. Si los costes del arbitraje son pequeños en relación a los costes de la negociación, entonces la partición negociada se aproxima a la propuesta por el árbitro, y en casos extremos el arbitraje es utilizado en equilibrio. Sin embargo, los jugadores no eligen siempre el método más eficiente de resolver su disputa: a veces negocian cuando es más eficiente acudir al arbitraje. En el capítulo 3 estudio los efectos de diferentes procedimientos arbitrales en el resultado de una negociación, en un modelo donde los jugadores realizan demandas no crecientes y el árbitro es llamado solo cuando las negociaciones se declaran rotas. Dos procedimientos arbitrales son analizados: el arbitraje convencional, donde el árbitro es libre de elegir su acuerdo y el arbitraje de oferta final, donde el árbitro está obligado a elegir una de las últimas ofertas de los jugadores. Demuestro que si los jugadores son suficientemente pacientes y el árbitro sigue un procedimiento de oferta final, en equilibrio, los jugadores negocian una partición pero toma algún tiempo llegar a ella. Sin embargo, si el árbitro sigue un procedimiento convencional, en equilibrio los jugadores utilizarán esta institución para resolver su disputa. Finalmente, en el capítulo 4 discuto el papel que juegan las opciones exteriores inciertas en las negociaciones cuando existe información incompleta acerca de su existencia. Examino una guerra de desgaste donde los jugadores disfrutan de información privada acerca de sus posibilidades de dejar la mesa de negociación para tomar una opción exterior. Hay dos tipos de jugadores: los tipos débiles, que no tienen opciones exteriores y prefieren conceder que salirse del juego, y los tipos fuertes que tienen opciones exteriores tales que prefieren salirse que conceder. El principal mensaje que surge del análisis de este juego es que la incertidumbre acerca de la posibilidad de que el oponente se vaya, mejora la eficiencia porque incrementa la probabilidad de concesión. Más precisamente, si la probabilidad de que el oponente sea fuerte es relativamente alta, la negociación acaba con una concesión segura. En el otro extremo, si la probabilidad de que el oponente sea débil es alta, los tipos fuertes dejarán en algún momento el juego con probabilidad igual a 1, dejando a los débiles jugando, desde ese momente en adelante el ineficiente equilibrio de la guerra de desgaste clásica. Incluso en este caso, la probabilidad de concesión a lo largo de la fase de incertidumbre del juego se incrementa.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Ciències Socials; Conventional arbitration; Final-offer arbitration; Negociación; Opciones exteriores

Procedural detachment in international commercial arbitration : the law applicable to arbitral procedure - Petrochilos, Georgios (University of Oxford, 2000)
This thesis seeks to ascertain the rules of private international law determining the procedural law of international commercial arbitral proceedings. In an Introduction, the author outlines the fundamental notions, introduces the topic and the major doctrines and issues, and sets out his methodology and structure of the work. The thesis examine first, as a preliminary issue, the considerations influencing the assumption of jurisdiction over arbitral proceedings. Chapter 1 discusses the various theories on the lex arbitri (the law supplying the general legal framework of an arbitration) as relevant to the procedural law, and concludes that they are deductive and therefore unable to satisfactorily to determine the applicable procedural law. Chapter 2 analyses major national laws as case-studies of the technique and scope of application of international arbitration law, and suggests a model of legislative and court jurisdiction based on the legal concept of 'seat of the arbitration' and on considerations based on the most appropriate court to control an arbitration. Chapter 3 discusses the obligations of the state of the seat under the European Convention on Human Rights and confirms the findings in Chapter 2. In a second part, the thesis elaborates on the title and extent of permissible municipal law interference. Chapter 4 tests the validity of the propositions derived from Chapters 2 and 3 against arbitral practice and concludes that seldom will arbitrators derogate from the law of the seat. Chapter 5 examines the particular case of arbitrations with states and similar entities. The third part discusses the relevance of compliance with the law of the seat at the stage of enforcement of an award. Chapter 6 deals with the technical issue of whether annulment at the place of making precludes enforcement in other fora. That chapter gives the opportunity to discuss models of separation of international jurisdiction and co-operation between different jurisdictions from a practical perspective. It thus serves as a convenient introduction to Chapter 7, which discusses the more abstract question of the nexus required between an arbitral award and the municipal law of the state of rendition in order for the award to enter, in limine, the scope of application of the international instruments in the field. The thesis ends with Conclusions in the form of model provisions for municipal law and arbitration rules.
Keywords: Arbitrage; Arbitragem; Arbitration; International commercial arbitration; Procédure arbitrale